118k views
0 votes
Y= 3x-1
2x+6=y substitution method

Y= 3x-1 2x+6=y substitution method-example-1

1 Answer

3 votes

Answer: (7, 20)

Concept:

There are three general ways to solve systems of equations:

  1. Elimination
  2. Substitution
  3. Graphing

Since the question has specific requirements, we are going to use substitution to solve the equations.

Solve:

Given equations

y = 3x - 1

2x + 6 = y

Substitute the y value since both equations has isolated [y]

2x + 6 = 3x - 1

Add 1 on both sides

2x + 6 + 1 = 3x - 1 + 1

2x + 7 = 3x

Subtract 2x on both sides

2x + 7 - 2x = 3x - 2x


\boxed{x=7}

Find the value of y

y = 3x - 1

y = 3(7) - 1

y = 21 - 1


\boxed{y=20}

Hope this helps!! :)

Please let me know if you have any questions

User Mostafa Vatanpour
by
5.6k points